2012
DOI: 10.4028/www.scientific.net/amr.433-440.530
|View full text |Cite
|
Sign up to set email alerts
|

Research on Machining Distortion due to Residual Stresses of Large Monolithic Beam

Abstract: Machining-induced distortion of large monolithic parts with thin walled structures creates problems in aircraft manufacturing industry. Typical monolithic beams of airframe are machined by NC machine and machining distortions are recorded. Thin walled structures are prone to distortions and dimensional instabilities due to internal stresses; therefore, stress-relieved vibration method is applied to reduce the internal stresses in blank material and results in better machining performance and dimension stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Ye et al, [25] concluded that more fluctuant residual stress distribution was found at the final path of milling on aeronautical monolithic components. Wang et al, [26] studied residual stresses during manufacturing stage. Actual machining distortion was measured after stress-relief using vibration aging method.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al, [25] concluded that more fluctuant residual stress distribution was found at the final path of milling on aeronautical monolithic components. Wang et al, [26] studied residual stresses during manufacturing stage. Actual machining distortion was measured after stress-relief using vibration aging method.…”
Section: Introductionmentioning
confidence: 99%